Conflicts about Social Justice and Education Certainty: An Education Philosophy Perspective - Muhammad Rafliyanto; Khozin Khozin (STAI Hubbulwathan Duri, 2025)
Education is widely regarded as a pathway to social justice and equality. However, in practice, structural inequalities persist, especially in developing countries like Indonesia. Despite national commitments to equitable education, significant disparities remain due to rigid standardization, centralized control, and limited responsiveness to local contexts. This study examines the philosophical tensions between social justice and educational certainty, drawing on the frameworks of John Rawls and Paulo Freire. This research employed a qualitative literature review method grounded in philosophical analysis. Key texts by Rawls and Freire were examined alongside Indonesian educational policy documents, constitutional principles, and contemporary studies. A thematic synthesis approach was used to analyze the convergence and divergence of liberal justice theory, critical pedagogy, and Indonesia’s juridical-ideological foundations. Findings reveal that educational certainty—often pursued through standardization and bureaucratic regulation—can contradict the principles of justice as fairness and emancipation. Rawls's institutional model emphasizes distributive justice and equal opportunity, while Freire's liberatory pedagogy focuses on critical consciousness and dialogical empowerment. In the Indonesian context, both perspectives highlight tensions between policy frameworks and lived educational experiences. This study proposes a reconciliatory framework that integrates Rawlsian and Freirean insights within Indonesia's constitutional philosophy. It argues for an education system that ensures structural equity while empowering learners as agents of transformation. The implications are relevant for educational policymakers, philosophers, and practitioners seeking socially just and context-sensitive reforms.